2020
DOI: 10.3390/ijerph17124231
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Lasher and Faulkender Anxiety about Aging Scale (AAS) for the Spanish Context

Abstract: Increased longevity has led to concerns and fears among the population about the inexorable process of ageing. This process causes individuals to become more anxious about the physical and psychosocial changes caused by the passage of time. However, there are currently no scales in the Spanish context that analyse ageing. Therefore, the aim of the present study is to validate the Anxiety about Aging scale to the Spanish context. In the present study, 594 subjects between 25 and 64 years old participated. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 36 publications
7
16
0
1
Order By: Relevance
“…The total variance extracted was high with amount of 59.1% supporting for content validity of the questionnaire. The findings were similar to those achieved in the original scale (Lasher & Faulkender, 1993), and also in several studies that have used the same instrument (Fernández-Jiménez et al, 2020). The model validity confirms the ability of revised 17-item AAS to discriminate and measure its dimensions: Fear of Old People, Psychological Concerns, Physical Appearance and Fear of Loss, across the youth population in Malaysia.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The total variance extracted was high with amount of 59.1% supporting for content validity of the questionnaire. The findings were similar to those achieved in the original scale (Lasher & Faulkender, 1993), and also in several studies that have used the same instrument (Fernández-Jiménez et al, 2020). The model validity confirms the ability of revised 17-item AAS to discriminate and measure its dimensions: Fear of Old People, Psychological Concerns, Physical Appearance and Fear of Loss, across the youth population in Malaysia.…”
Section: Discussionsupporting
confidence: 84%
“…Namely five instruments are developed for various age groups including younger adults which are Personal Experience of Ageing (Steverink, Westerhof, Bode, & Dittmann-Kohli, 2001), Attitude-Aging-Visual Analogue Scales (Ligon, Ehlman, Moriello, Russo, & Miller, 2014), Reactions to Ageing Questionnaire (Gething, 1994), Personal Anxiety toward Ageing (Kafer, Rakowskl, Lachman, & Hickey, 1980) and Anxiety about Aging Scale (AAS) (Lasher & Faulkender, 1993). Among the mentioned instruments, AAS is the widely used and appropriate instrument to assess fear of aging (Fernández-Jiménez, Álvarez-Hernández, Salguero-García, Aguilar-Parra, & Trigueros, 2020).…”
Section: Anxiety About Aging Scale (Aas)mentioning
confidence: 99%
“…Previous studies also supported the four-factor structure of the AAS [7,[22][23][24]. However, our study was the rst study to apply it particularly on the elderly adults.…”
Section: Discussionsupporting
confidence: 76%
“…The results of the study revealed that the AAS items were invariant across gender and living status among subgroups of the participants. Consistent with previous studies [24,25], the AAS can be conveniently applied for gender groups as well as the living conditions of the elderly in Iran.…”
Section: Discussionsupporting
confidence: 75%
“…Values > 0.5 and >0.7 for AVE and CR indicate evidence of the convergent validity of the AAS. To further assess the AAS, Rasch analyses were performed using the partial credit model [ 15 , 16 , 17 , 18 ]. Item fit in the Rasch model was evaluated using information-weighted fit statistic (infit) mean square (MnSq) and outlier-sensitive fit statistic (outfit) MnSq.…”
Section: Methodsmentioning
confidence: 99%